Free Open Access Science: A Challenging Future - Committee, Editorial (Austral Journal of Veterinary Sciences, 2017)
The situation arises all over the world and that it is due to our seeking out journals with high ISI impact, with the aim that our research work be published, yet without considering the visibility these publications may have in the areas where the studies were performed. Despite this, many researchers remain active, publishing work that can never be read by those who might be most interested, or by teaching staff at universities that have not subscribed to certain journals. This situation is repeated by researchers aiming to increase their chances of being granted funding for their projects, and then going on to repeat these practices.